Mini Transsternal Approach to the Anterior High Thoracic Spine (T1–T4 Vertebrae). (27th April 2016) - Brogna, Christian; Thakur, Bhaskar; Fiengo, Leslie; Tsoti, Sandra Maria; Landi, Alessandro; Anichini, Giulio; Vergani, Francesco; Malik, Irfan
Abstract : Purpose . The anterior high thoracic spine is one of the most complex segments to be accessed surgically due to anatomical constraints and transitional characteristics. We describe in detail the mini transsternal approach to metastatic, infective, traumatic, and degenerative pathologies of T1 to T4 vertebral bodies. We analyse our surgical series, indications, and outcomes. Methods . Over a 5-year period 18 consecutive patients with thoracic myelopathy due to metastatic, infective, traumatic, and degenerative pathologies with T1 to T4 vertebral bodies involvement received a mini transsternal approach with intraoperative monitoring. Frankel scoring system was used to grade the neurological status. Results . Mean follow-up was 40 months. 78% patients improved in Frankel grade after surgery and 22% patients remained unchanged. Average operation time was 210 minutes. There were no intraoperative complications. One patient developed postoperative pneumonia successfully treated with antibiotics. Conclusion . The mini transsternal is a safe approach for infective, metastatic, traumatic, and degenerative lesions affecting the anterior high thoracic spine and the only one allowing an early and direct visualisation of the anterior theca. This approach overcomes the anatomical constraints of this region and provides adequate room for optimal reconstruction and preservation of spinal alignment in the cervicothoracic transition zone with good functional patient outcomes.